Comparative Analysis of the Outcomes of Laparoscopic Right Hemicolectomy with D2 and D3 Lymphadenectomy in the Treatment of Patients with Right Colon Cancer - A. A. Nevolskikh; V. A. Avdeenko; Yu. Yu. Mikhaleva; T. P. Pochuev; P. V. Sokolov; R. F. Zibirov; I. P. Reznik; N. D. Silin; L. O. Petrov; S. A. Ivanov; A. D. Kaprin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Introduction. The standard volume of removed groups of lymph nodes for right colon cancer (RCC) has not been determined. According to Japanese clinical guidelines, it is necessary to perform D3 lymphadenectomy in all cases, except stage I, while according to European and Russian clinical guidelines, the standard scope of surgical intervention includes only D2 lymphadenectomy. There are no long-term results regarding differences between D2 and D3 lymph node dissection in RCC; therefore, it is relevant to conduct studies to improve the long-term results of treatment of patients with RCC.Aim: to comparatively evaluate the results of treatment of patients with RCC who underwent laparoscopic right hemicolectomy at A. Tsyb Medical Radiological Research Center.Materials and methods. Conducted from 2018 to 2023, the study included 174 patients with stage I–III RCC: in 106 patients, laparoscopic right hemicolectomy with D2 lymph node dissection was performed, in 68 patients — with D3 lymph node dissection. When assessing the homogeneity and comparability of the groups, according to input parameters, such as clinical stage, gender, age, body mass index and tumor location, their heterogeneity was noted, which did not allow a direct comparative assessment of both groups. To eliminate heterogeneity and adequately select groups, a pseudorandomization technique was used, after which the groups (n = 68) became statistically comparable in all main clinical parameters.Results. Statistically significant differences were obtained in the median duration of surgical intervention, which was longer in the group of patients with D3 lymph node dissection — 150 (60–393) and 213 (70–390) minutes (p < 0.001), and in the median time of flatus passage — 2 (1–4) and 3 (1–9) days, respectively (p = 0.042). Postoperative complications in accordance with the Clavien — Dindo classification occurred in 16 (23.5 %) patients in the group with D2 and in 15 patients (22.1 %) in the group with D3 lymph node dissection (p = 0.999); III–V grade complications were noted in 2 (2.9 %) cases in each group (p = 0.999). Postoperative hospital stay was 6 days for patients in both groups (p = 0.369). During pathomorphological assessment of the removed specimen, the median number of examined lymph nodes was significantly higher in the group with D3 lymph node dissection: 14 (1–52) and 19 (3–59) lymph nodes, respectively (p < 0.001). Involvement of apical lymph nodes (groups 203, 213, 223) was noted in 2 (3 %) patients. In the group with D2 lymph node dissection, distant metastases were recorded twice as often as in the group with D3 lymph node dissection — in 8 (11.8 %) and 4 (5.9 %) patients, respectively (p = 0.365). Local recurrence was not established in any case. The three-year overall and disease-free survival rates were 94.8 ± 3.0 and 100 % (p = 0.149) and 80.5 ± 5.8 and 88.7 ± 5.8 % (p = 0.177), respectively.Conclusions. The experience of using total mesocolonectomy with D3 lymph node dissection for RCC indicates the safety of this surgical intervention in comparison with traditional surgical techniques, while we did not obtain statistically significant differences in patient survival. To definitively determine the role of D3 lymph node dissection in the treatment of patients with RCC, large multicenter randomized studies are certainly needed.